2016
DOI: 10.3390/genes7080054
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of Retinoic Acid Receptor-Related Orphan Receptor Alpha Determine Susceptibility to Type 2 Diabetes Mellitus in Han Chinese

Abstract: Retinoic acid receptor-related orphan receptor alpha (RORA) plays a key role in the regulation of lipid and glucose metabolism and insulin expression that are implicated in the development of type 2 diabetes mellitus (T2DM). However, the effects of genetic variants in the RORA gene on the susceptibility to T2DM remain unknown. Nine tagging single-nucleotide polymorphisms (SNPs) were screened by using the SNaPshot method in 427 patients with T2DM and 408 normal controls. Association between genotypes and haplot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
(58 reference statements)
1
12
0
Order By: Relevance
“…Development of the high-throughput single nucleotide polymorphism (SNP) genotyping technology and completion of the HapMap project enabled the implementation of genome-wide association studies (GWAS) [ 7 ] and since 2007 they have become the leading tool for the identification of several T2D susceptibility loci [ 2 , 8 ]. Recent GWAS, initially performed in Caucasians and then in non-European populations, and meta-analyses of these studies, have increased the total number of the identified variants with possible association to over 88 variants, including and further confirming some variants that were previously identified by the linkage and candidate gene studies [ 9 , 10 ]. However, additional variants are likely to be discovered since the identified associations explain only about 10% of the heritability of the disease [ 2 , 4 , 8 ].…”
Section: Introductionmentioning
confidence: 76%
“…Development of the high-throughput single nucleotide polymorphism (SNP) genotyping technology and completion of the HapMap project enabled the implementation of genome-wide association studies (GWAS) [ 7 ] and since 2007 they have become the leading tool for the identification of several T2D susceptibility loci [ 2 , 8 ]. Recent GWAS, initially performed in Caucasians and then in non-European populations, and meta-analyses of these studies, have increased the total number of the identified variants with possible association to over 88 variants, including and further confirming some variants that were previously identified by the linkage and candidate gene studies [ 9 , 10 ]. However, additional variants are likely to be discovered since the identified associations explain only about 10% of the heritability of the disease [ 2 , 4 , 8 ].…”
Section: Introductionmentioning
confidence: 76%
“…RORα gene has known to play an important role in the regulation of lipid and glucose metabolism and insulin expression that are involved in the development of T2D. Researchers in [24] suggested that the genetic variation in RORα gene might be an indication to the individual's susceptibility to T2D. This indicates that the effect of rs10519107 to the susceptibly to T2D could show risk association if it is investigated in another ethnicity populations.…”
Section: Discussionmentioning
confidence: 98%
“…The RORA gene is considered a predisposing gene for diabetes in Mexican Americans ( Hayes et al , 2007 ). Furthermore, mutation of an individual base in this gene is positively correlated with incidence of diabetes in the Chinese population ( Zhang et al , 2016 ). The protein encoded by the FDFT1 gene is the first enzyme in cholesterol biosynthesis, and studies have found that this gene can affect blood lipids, blood sugar, and inflammation, thus participating in obesity-related coronary heart disease, diabetes, and coronary artery calcification ( Ding et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%